Modelagem da temperatura da superfície urbana em função da cobertura vegetal e do extrato populacional de municípios paulistas - (:unkn) unknown (Universidade Brasil, 2020)
With the passing of time, it becomes increasingly evident that cities should think of trees and plant components as urban infrastructure for public health and well-being of the population as a whole. The changes in the physical environment caused by the growing population agglomeration made the characteristics of environmental and urban life unsatisfactory. In order to assess the well-being of the population, indicators were created addressing aspects related to economic, social and environmental conditions, such as the percentage of vegetation cover (VC), tree cover (TC) and green areas (GA). The VC is the sum of the entire vegetated area of a municipality, that is, GA’s and TC. GA’s comprise flowerbeds, gardens, etc., except for trees. TC, on the other hand, is restricted only to the area of tree crowns. According to the Resolution of the Secretariat for the Environment of the State of São Paulo Resolution no. 33/2018, the ideal goal of VC in a city is 50%. It is known that vegetation decreases the local average temperature due to physical and physiological factors, such as photosynthesis, evapotranspiration and shading and that, according to the literature, increases in urban VC are able to decrease surface temperature. Thus, the objective of this research was to evaluate the variation in the temperature of the urban surface as a function of the VC by mathematical models and to quantify the optimal percentage of coverage in the urban area according to the population extract of the municipality. Fifteen towns in the state of São Paulo were chosen at random, and then split into five population extracts with three towns in each. Towns with up to 20,000 inhabitants (Estrela d'Oeste, Pompéia and Santo Antônio do Aracanguá), towns with 20,001 to 50,000 inhabitants (Descalvado, Tanabi and Valparaíso), towns with 50,001 to 100,000 inhabitants (Fernandópolis, Mirassol and Paulínia), towns with 100,001 to 500,000 inhabitants (Araraquara, São José do Rio Preto and Sorocaba), and towns with over 500,000 inhabitants (Campinas, Santo André and São José dos Campos). Sample fields were defined and distributed in the various municipalities on current images of Google Earth Pro, where the VC areas were delimited by manual scanning and were later confronted with thermal images. The modeling of the urban surface temperature as a function of vegetation cover was performed by statistical regression. The conclusion was that the TC was more effective to reduce urban surface temperature than the percentage of GA or VC. According to the models proposed, a percentage of TC of 50% would be able to reduce by 4°C the temperature of towns with over 20,000 inhabitants in the state of São Paulo. Such percentage should be spread throughout the urban environment. The general mean of the percentage of GA, TC and VC in all population extracts was 11.9%, 13.5% and 25.2% respectively. There were no significant differences among the extracts. The index of 50% VC proposed by the Secretariat of Infrastructure and Environment of the state of São Paulo (SIMA, ex-SMA) can be considered appropriate to reduce urban temperature, provided that only the crowns of the trees are quantified.
Keywords: Urbanização; Árvores; Cobertura arbórea; Áreas verdes; CB